AB1061 Comparing four imaging techniques of visualzing gouty tophi using one single patient. (23rd January 2014) - Su, H.; Li, X.; Zhao, N.; Yu, D.
Abstract : Background: Gouty arthritis-causing uric acid is persistently in excess in the form of tophi. The ultimate therapeutic ideal should be to completely eliminate all tophi. So far, clinicians have relied on physical examination and plain radiographs to assess the locations and sizes of Gouty tophi. The dual energy computerized tomography (DECT), magnetic resonance imaging (MRI), 2-fluoro-deoxy-D-glucose (FDG) positron emission tomography (PET) each offers a different perspective of gouty tophi. None of the papers have used all four techniques concomitantly, no guidelines are available concerning their applications. Objectives: To visualize in a gout patient, using four different imaging techniques, the locations, sizes, compactness of tophi. Methods: The feet and knees were imaged by X-ray, MRI, DECT and PET. Results: DECT uncovered deposits in unexpected locations. The combination of DECT, MRI and PET showed that tophi were much larger and more inflammatory than clinically suspected. Conclusions: The locations and sizes of tophi in chronic gout patients can far exceed those accessible by physical examination and X-ray. These can be critical when making decisions concerning the initiation and aggressiveness of serum uric acid- lowering therapies. References: Neogi T. Clinical practice. Gout. N Engl J Med. 2011 Feb 3;364(5):443-52. Dalbeth N, McQueen FM. Use of imaging to evaluate gout and other crystal deposition disorders. Curr Opin Rheumatol. 2009 Mar;21(2):124-31. Choi HK, Al-Arfaj AM, Eftekhari A, Munk PL, Shojania K, Reid G, et al. Dual energy computed tomography in tophaceous gout. Ann Rheum Dis. 2009 Oct;68(10):1609-12. Nicolaou S, Yong-Hing CJ, Galea-Soler S, Hou DJ, Louis L, Munk P. Dual-energy CT as a potential new diagnostic tool in the management of gout in the acute setting. AJR Am J Roentgenol. 2010 Apr;194(4):1072-8. Ko KH, Hsu YC, Lee HS, Lee CH, Huang GS. Tophaceous gout of the knee: revisiting MRI patterns in 30 patients. J Clin Rheumatol. 2010 Aug;16(5):209-14. Disclosure of Interest: None Declared